A survey of arsenic, mercury, cadmium, and lead residues in seafood (fish, crustaceans, and cephalopods) from the south‐eastern Mediterranean Sea. Issue 3 (13th February 2021) - Ramon, Debra; Morick, Danny; Croot, Peter; Berzak, Ran; Scheinin, Aviad; Tchernov, Dan; Davidovich, Nadav; Britzi, Malka
Abstract: Seafood is capable of bioaccumulating heavy metals (HM), making it a potentially major dietary source of HM for humans. Presently, little data exists on seafood from the eastern‐most boundary of the Mediterranean Sea. This study aims to provide exposure insight of the Israeli population to HM through the consumption of locally caught seafood by assessing the levels of arsenic, mercury, cadmium, and lead in raw tissues of seafood. A wide survey of local fisheries was conducted providing 296 samples from 11 different species, including seven fish, two crustacean, and two cephalopod species. Total arsenic, cadmium, and lead were analyzed by graphite‐furnace atomic absorption. Total mercury was measured by cold‐vapor mercury analyzer. Arsenic speciation was performed by anion chromatography‐inductively coupled plasma sector field mass spectrometry. Results suggested that the total arsenic concentrations were significantly higher in crustaceans and cephalopods than fish. Arsenic speciation revealed two samples that exceed 1 mg/kg of inorganic arsenic, whereas methylated arsenic was below the detection limit. Elevated mercury levels were detected in the commercial benthic species Mullus barbatus (red mullet), cadmium was detected in one‐third of the samples, and lead detected in eight samples. Comparing the results to health guidelines, 99.4% of seafood tested in this study abide with acceptable levels of heavy metals in seafood, as defined by both Israeli and European Union guidelines.